The Influence of Traffic, Area Location, and Other Factors on Operating Room Microbial Load. (15th February 2018) - Taaffe, Kevin; Lee, Brandon; Ferrand, Yann; Fredendall, Lawrence; San, Dee; Salgado, Cassandra; Shvorin, Dotan; Khoshkenar, Amin; Reeves, Scott
Abstract : OBJECTIVE: To determine how the movement of patients, equipment, materials, staff, and door openings within the operating room (OR) affect microbial loads at various locations within the OR. DESIGN: Observation and sampling study. SETTING: Academic health center, public hospital. METHODS: We first analyzed 27 videotaped procedures to determine the areas in the OR with high and low numbers of people in transit. We then placed air samplers and settle plates in representative locations during 21 procedures in 4 different ORs during 2 different seasons of the year to measure microbial load in colony-forming units (CFU). The temperature and humidity, number of door openings, physical movement, and the number of people in the OR were measured for each procedure. Statistical analysis was conducted using hierarchical regression. RESULTS: The microbial load was affected by the time of year that the samples were taken. Both microbial load measured by the air samplers and by settle plates in 1 area of the OR was correlated with the physical movement of people in the same area but not with the number of door openings and the number of people in the OR. CONCLUSIONS: Movement in the OR is correlated with the microbial load. Establishing operational guidelines or developing OR layouts that focus on minimizing movement by incorporating desirable internal storage points and workstations can potentially reduce microbial load, thereby potentially reducing surgical site infection risk. Infect Control Hosp Epidemiol 2018;39:391–397